Ages of evolved low mass stars: Central stars of planetary nebulae and white dwarfs - Costa R.D.D.; Rodrigues T.S.; Maciel W.J. (EPJ Web of Conferences, 2013)
We have developed several methods to estimate the ages of central stars of planetary nebulae (CSPN), which are based either on observed nebular properties or on data from the stars themselves. Our goal is to derive the age distribution of these stars and compare the results with empirical distributions for CSPN and white dwarfs. We have initially developed three methods based on nebular abundances, using (i) an age-metallicity relation which is also a function of the galactocentric distance; (ii) an age-metallicity relation obtained for the galactic disk, and (iii) the central star masses derived from the observed nitrogen abundances. In this work we present two new, more accurate methods, which are based on kinematic properties: (I) in this method, the expected rotation velocities of the nebulae around the galactic centre at their galactocentric distances are compared with the predicted values for the galactic rotation curve, and the differences are attributed to the different ages of the evolved stars; (II) we determine directly the U, V, W, velocity components of the stars, as well as the velocity dispersions, and use the dispersion-age relation by the Geneva-Copenhagen survey. These methods were applied to two large samples of galactic CSPN. We conclude that most CSPN in the galactic disk have ages under 5 Gyr, and that the age distribution is peaked around 1 to 3 Gyr.